Diseases of the chest, heart and vascular system 2025-2028. Diagnostic imaging - Hodler, Jürg; Kubik-Huch, R. A.; Roos, Justus E. (Cham : Springer, 2025)
This open access book offers an essential overview of chest, heart and vascular system imaging. Over the last few years, there have been considerable advances in this area, driven by both clinical and technological developments. Written by leading international experts and teachers, the chapters are disease-oriented and cover all relevant imaging modalities, with a focus on magnetic resonance imaging and computed tomography. IDKD books are rewritten (not merely updated) every four years, which means they offer a comprehensive review of the state-of-the-art in imaging. The book is clearly structured and features learning objectives, abstracts, subheadings, tables and take-home points, supported by design elements to help readers navigate the text. It will particularly appeal to general radiologists, radiology residents, and interventional radiologists who want to update their diagnostic expertise, as well as clinicians from other specialties who are interested in imaging for their patient care.
Airways and Inhalational Lung Disease -- Mastering Mediastinal Imaging: Tips, Tricks, and Key Diagnoses -- Current Concepts in the Diagnosis and Staging of Lung Cancer -- Diseases of the Pleura and Chest Wall -- Pulmonary Manifestations of Systemic Diseases -- Congenital Heart Disease in Adults -- Pulmonary Vascular Disease -- Fibrosing Interstitial Lung Disease -- Imaging in patients with non-fibrosing interstitial lung diseases -- Imaging of Chest Trauma.-Challenges in Thoracic Oncological Interpretation -- Diagnosis of Focal Lung Disease -- Micronodular Lung Disease -- Challenging Chest Radiograph Interpretation -- Endovascular Aortic Repair: What the Interventionalist Needs to Know from the Radiologist -- Cardiac CT: Coronary, Valves and Function -- Cardiac MR for the Non-Cardiac Radiologist -- Pulmonary Infections.-Chest Manifestation of Cardiac Disease -- Pediatric and Adolescent Lung Diseases.
Online resource; title from PDF title page (SpringerLink, viewed March 6, 2025).
Springer Nature
Keywords: Heart -- Imaging; Chest -- Diseases -- Imaging; Lungs -- Diseases -- Imaging; Chest -- Diseases; Lungs -- Diseases; Thoracic Diseases; Lung Diseases; Cœur -- Imagerie; Thorax -- Maladies; Poumons -- Maladies; Electronic books